2000
DOI: 10.1038/35036627
|View full text |Cite
|
Sign up to set email alerts
|

The large-scale organization of metabolic networks

Abstract: An important goal in biology is to uncover the fundamental design principles that provide the common underlying structure and function in all cells and microorganisms [6][7][8][9][10][11][12][13] . For example, it is increasingly appreciated that the robustness of various cellular processes is rooted in the dynamic interactions among its many constituents [14][15][16] , such as proteins, DNA, RNA, and small molecules.Recent scientific developments improve our ability to identify the design principles that inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

54
1,811
5
16

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 4,089 publications
(1,886 citation statements)
references
References 24 publications
54
1,811
5
16
Order By: Relevance
“…The simultaneous emergence of an inhomogeneous structure in both metabolic- 5,11 and protein interaction networks indicates the evolutionary selection of a common large scale structure of biological networks, and strongly suggests that future systematic protein-protein interaction studies in other organisms will uncover an essentially identical protein network topology. The correlation between the connectivity and indispensability of a given protein confirms that despite the importance of individual biochemical function and genetic redundancy, the robustness against mutations in yeast is also derived from the organization of interactions and topologic position of individual proteins 12 .…”
mentioning
confidence: 99%
“…The simultaneous emergence of an inhomogeneous structure in both metabolic- 5,11 and protein interaction networks indicates the evolutionary selection of a common large scale structure of biological networks, and strongly suggests that future systematic protein-protein interaction studies in other organisms will uncover an essentially identical protein network topology. The correlation between the connectivity and indispensability of a given protein confirms that despite the importance of individual biochemical function and genetic redundancy, the robustness against mutations in yeast is also derived from the organization of interactions and topologic position of individual proteins 12 .…”
mentioning
confidence: 99%
“…We refer to this network representation as the finite-state representation, by analogy with finite-state machines, 61 and contrast it with the commonly used representations of metabolic networks as interaction networks, in which individual metabolites are network nodes and network edges connect all reaction participants with each other. 5,32,62,63 The finite-state representation of the reaction network is a directed network with edge weights given by thermodynamic and / or kinetic parameter values.…”
Section: Probing the Chemistry Of The Formose Reaction Networkmentioning
confidence: 99%
“…1,2 Characteristic features of complex reactions include branching and interference of reaction pathways, autocatalysis, and product inhibition and are observed in systems as varied as transition-metal catalysis, 3 cell metabolism, 4,5 and polymerization. 1,6,7 A better understanding of the network effects in these complex reactions offers means for influencing their dynamics and product composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying diverse biological systems, it has been shown that biochemical pathways are not arranged with random numbers of connectivities; instead, they display a scale-free character [1]. A crucial characteristic of this type of system is that it is largely controlled by a few hubs or nexuses, which dominate the overall connectivity and stability of the graph.…”
Section: Introductionmentioning
confidence: 99%